2023
DOI: 10.3390/nu15081947
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Sources, Identification/Quantification Methods, Health Benefits, Bioaccessibility, and Products of Isorhamnetin Glycosides as Phytonutrients

Abstract: In recent years, people have tended to consume phytonutrients and nutrients in their daily diets. Isorhamnetin glycosides (IGs) are an essential class of flavonoids derived from dietary and medicinal plants such as Opuntia ficus-indica, Hippophae rhamnoides, and Ginkgo biloba. This review summarizes the structures, sources, quantitative and qualitative analysis technologies, health benefits, bioaccessibility, and marketed products of IGs. Routine and innovative assay methods, such as IR, TLC, NMR, UV, MS, HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 222 publications
0
7
0
Order By: Relevance
“…The greatest activity highlighted for the flower Spp-ETAC fraction could be related to the presence of Isorhamnetin derivatives, particularly of Isorhamnetin glucoside, not detected in the other characterized fractions; indeed, several in vitro and in vivo investigations have demonstrated the strong antioxidant and radical-scavenging properties of Isorhamnetin glucosides, supporting their use as phytonutrients. [32] In a previous study conducted by Jia and colleagues, 1-O-Feruloyl-β-D-glucose was shown to exhibit weak DPPH radical scavenging ability and moderate reducing power; this could explain the lower antioxidant properties of the leaf Spp-ETAC fraction, despite the high quantity of 1-O-Feruloyl-β-D-glucose, equal to about onethird of the total content of phenolic compounds detected in the fraction. [33] On the other hand, phenolic-rich fractions did not display any ferrous ion chelating activity, which instead was highlighted for the more hydrophobic ones.…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…The greatest activity highlighted for the flower Spp-ETAC fraction could be related to the presence of Isorhamnetin derivatives, particularly of Isorhamnetin glucoside, not detected in the other characterized fractions; indeed, several in vitro and in vivo investigations have demonstrated the strong antioxidant and radical-scavenging properties of Isorhamnetin glucosides, supporting their use as phytonutrients. [32] In a previous study conducted by Jia and colleagues, 1-O-Feruloyl-β-D-glucose was shown to exhibit weak DPPH radical scavenging ability and moderate reducing power; this could explain the lower antioxidant properties of the leaf Spp-ETAC fraction, despite the high quantity of 1-O-Feruloyl-β-D-glucose, equal to about onethird of the total content of phenolic compounds detected in the fraction. [33] On the other hand, phenolic-rich fractions did not display any ferrous ion chelating activity, which instead was highlighted for the more hydrophobic ones.…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…Similar to quercetin, isorhamnetin is found bound to saccharides, and in stinging nettle, it is found as isorhamnetin-3- O -glucoside and isorhamnetin-3- O -rutinoside (glycoside of isorhamnetin and α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranose). Isorhamnetin has antimicrobial, antioxidant, anti-inflammatory, and anti-carcinogenic effects [ 136 ]. Similarly to quercetin, isorhamnetin is an effective ROS and free radical scavenger.…”
Section: Bioactivity Of Phenolic and Polyphenolic Compounds In Stingi...mentioning
confidence: 99%
“…Rutin exhibits antidiabetic properties by inhibiting small intestine carbohydrate absorption, increasing tissue glucose consumption, and stimulating insulin secretion [52]. Some isorhamnetin glycosides exhibit antioxidant, anti-inflammatory, anti-cancer, and antidiabetic activities [53]. Diosmetin 7-rutinoside is also named diosmin, which has demonstrated its ability to lower plasma glucose levels and increase plasma insulin levels in diabetic rats.…”
Section: Fermented Ntf Product Displays Anti-diabetic Potentialmentioning
confidence: 99%